Determinants to Enhance the Sustainable Business of Islamic Banks: A Comprehensive Review for Future Research Agenda - Mohammad Yamin; Indra Siswanti; Augustina Kurniasih; Yudhi Herliansyah (Amkop Management Accounting Review (AMAR), 2026)
The sustainability of Islamic banks has received growing scholarly attention; however, its long-term determinants remain theoretically fragmented across governance, risk, innovation, and ethical domains. This systematic literature review synthesizes 68 peer-reviewed articles published between 2021 and 2025 to critically consolidate the structural drivers of sustainable business in Islamic banking. Addressing five interrelated research questions, the findings demonstrate that sustainability does not depend on isolated financial indicators. Rather, it emerges from the systemic interaction between internal governance mechanisms particularly Islamic corporate governance, operational efficiency, and innovation capacity and external institutional pressures, including environmental regulation, market dynamics, and alignment with the Sustainable Development Goals (SDGs). The literature shows persistent analytical fragmentation and limited operational integration between global sustainability standards and Islamic ethical objectives. Digital transformation has become an increasingly important strategic enabler, yet it remains institutionally secondary to governance, corporate social responsibility, and sustainable financing factors. Risk management, especially financing risk, consistently underpins long-term stability, while evidence on capital adequacy and liquidity remains inconclusive. By proposing an integrated sustainability architecture linking financing risk, green financing, digital transformation, Islamic corporate governance, and environmental regulation, this study reframes the discourse and offers a theoretically grounded basis for future empirical and policy development.